1989
DOI: 10.1161/01.str.20.9.1156
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fludrocortisone acetate in patients with subarachnoid hemorrhage.

Abstract: In this study with randomized controls, we administered fludrocortisone acetate to 46 of 91 patients with subarachnoid hemorrhage in an attempt to prevent excessive natriuresis and plasma volume depletion. Fludrocortisone significantly reduced the frequency of a negative sodium balance during the first 6 days (from 63% to 38%, p = 0.041). A negative sodium balance was significantly correlated with decreased plasma volume during both the first 6 days (p = 0.014) and during the entire 12-day study period (p = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(87 citation statements)
references
References 26 publications
4
78
1
2
Order By: Relevance
“…494 In several uncontrolled studies, the development of volume contraction was found to be ameliorated by the administration of large amounts of fluids (hypervolemic therapy). 493,495 Two randomized, controlled trials have been performed to evaluate the ability of fludrocortisone to correct hyponatremia and fluid balance. One found that it helped to correct the negative sodium balance but not volume contraction or hyponatremia, 495 and the other reported a reduced need for fluids and improved sodium levels with fludrocortisone.…”
Section: Management Of Hyponatremia and Volume Contractionmentioning
confidence: 99%
See 1 more Smart Citation
“…494 In several uncontrolled studies, the development of volume contraction was found to be ameliorated by the administration of large amounts of fluids (hypervolemic therapy). 493,495 Two randomized, controlled trials have been performed to evaluate the ability of fludrocortisone to correct hyponatremia and fluid balance. One found that it helped to correct the negative sodium balance but not volume contraction or hyponatremia, 495 and the other reported a reduced need for fluids and improved sodium levels with fludrocortisone.…”
Section: Management Of Hyponatremia and Volume Contractionmentioning
confidence: 99%
“…493,495 Two randomized, controlled trials have been performed to evaluate the ability of fludrocortisone to correct hyponatremia and fluid balance. One found that it helped to correct the negative sodium balance but not volume contraction or hyponatremia, 495 and the other reported a reduced need for fluids and improved sodium levels with fludrocortisone. 496 One retrospective study has suggested that 3% saline is effective in correcting hyponatremia.…”
Section: Management Of Hyponatremia and Volume Contractionmentioning
confidence: 99%
“…Volume contraction has been linked to symptomatic vasospasm [18], and fluid restriction has been associated with an increased incidence of delayed ischemic deficits [16]. In several uncontrolled studies, the development of volume contraction was found to be ameliorated by the administration of large amounts of fluids [17,19]. In another study, however, only hyponatremia but not decreased circulating blood volume was prevented by administration of large amounts of sodium and water, adapted to renal excretion [20].…”
Section: Discussionmentioning
confidence: 99%
“…One trial found that it helped to correct the negative sodium balance, and the other reported a reduced need for fluids and improved sodium levels using this mineralocorticoid. 305,306 A similar randomized, placebo-controlled trial showed reduced natriuresis and a lower rate of hyponatremia in aSAH patients treated with hydrocortisone. 307 The value of albumin as an efficient volume expander during the vasospasm phase in aSAH has been suggested in uncontrolled studies, but there is no clear evidence of its superiority over crystalloids in patients with aSAH.…”
Section: Management Of Medical Complications Associated With Asahmentioning
confidence: 98%